PMO-057 Dietary intervention for individuals with spinal cord injuries—a 2 year report on the spinal clinic for obese out-patient project (scoop). (28th May 2012) - Wong, S S H; Graham, A; Jamous, A; Spillman, L; Grimble, G; Forbes, A
Abstract : Introduction: Obesity is common after spinal cord injuries (SCI) 1 and it is associated with chronic nutrition related complications. We previously reported that a simple dietetic-intervention can help SCI patients to lose weight without compromising lean body mass. 2 Methods: The present study aimed to assess the effectiveness of a dietitian led weight management clinic. Thirty-one individuals (52.4±11.5 years; body mass index (BMI): 32.9 kg/m 2 ; 41% female) with SCI were referred for consultation to include nutritional advice and cognitive behaviour therapy in three consultations over 4 months. Outcomes measures included body composition from anthropometric measurements of BMI, mid upper-arm circumference (MUAC), triceps skinfold thickness (TSF) and mid-arm muscle circumference (MAMC), sitting blood pressure and dietary assessment of nutrient intake by 7-d food diary. Results: Of the thirty-one individuals, 15 (48.4%) reported one or more co-morbidities. Mean weight loss was 4.5 kg (SD 6.2) at week 16. Analysis of the pre- to post-intervention difference (using paired t-test) showed a significant reduction in weight (104.2 vs 100.4 kg, p=0.001), BMI (34 vs 33.1 kg/m 2, p=0.004), total energy intake (6.84 vs 5.62 MJ/d, p=0.029), total fat (p=0.005), saturated fat (p=0.001) and alcohol (p=0.003). No significant changes were found in MUAC, TSF, MAMC and sitting blood pressure post intervention. We noted a significant reduction in MAMC at 1-year follow-up (30.2 vs 27.1 cm, p<0.001). The 7-d food diary showed an average energy intake of 7.65 MJ/d, which is 15% below the estimated requirement. Conclusion: The findings of this study suggest that current guidance overestimates nutritional requirements in the SCI population, and that simple dietetic-intervention could help overweight SCI patients to achieve weight loss, but that it may not be sufficient to stimulate/maintain muscle mass long term. Further research is warranted to test whether combining lifestyle and intensive physical therapy could reduce long-term muscle wasting. Competing interests: None declared. References: 1. Gupta N, et al. Spinal Cord 2006;44 :92–4. 2. Wong S, et al. Food Nutr Sci 2011;2 :901–7.